Phoenixin 14 Inhibits High-Fat Diet-Induced Non-Alcoholic Fatty Liver Disease in Experimental Mice - Yang F; Huang P; Shi L; Liu F; Tang A; Xu S (Dove Medical Press, 2020)
Fan Yang,1 Ping Huang,1 Liandong Shi,2 Feng Liu,3 Aimei Tang,3 Shaohui Xu1 1Department of Endocrinology, Guilin People’s Hospital, Guilin, Guangxi 541002, People’s Republic of China; 2Department of Ultrasonography, Guilin People’s Hospital, Guilin, Guangxi 541002, People’s Republic of China; 3Department of Ministry of Health Care, Guilin People’s Hospital, Guilin, Guangxi 541002, People’s Republic of ChinaCorrespondence: Fan YangDepartment of Endocrinology, Guilin People’s Hospital, No. 12, Wenming Road, Guilin, Guangxi 541002, People’s Republic of ChinaTel/ Fax +86-773-2821218Email fanyang823@163.comIntroduction: Nonalcoholic fatty liver disease (NAFLD) is one of the most common chronic liver diseases. The development of NAFLD is closely associated with hepatic lipotoxicity, inflammation, and oxidative stress. The new concept of NAFLD treatment is to seek molecular control of lipid metabolism and hepatic redox hemostasis. Phoenixin is a newly identified neuropeptide with pleiotropic effects. This study investigated the effects of phoenixin 14 against high-fat diet (HFD)-induced NAFLD in mice.Materials and Methods: For this study, we used HFD-induced NAFLD mice models to analyze the effect of phonenixin14. The mice were fed on HFD and normal diet and also given phoenixin 14 (100 ng/g body weight) by gastrogavage for 10 weeks. The peripheral blood samples were collected for biochemical assays. The liver tissues were examined for HFD-induced tissue fibrosis, lipid deposition and oxidative activity including SOD, GSH, and MDA. The liver tissues were analyzed for the inflammatory cytokines and oxidative stress pathway genes.Results: The results indicate that phoenixin 14 significantly ameliorated HFD-induced obesity and fatty liver. The biochemical analysis of blood samples revealed that phoenixin 14 ameliorated HFD-induced elevated circulating alanine aminotransferase (ALT), aspartate aminotransferase (AST), total cholesterol, and triglyceride levels, suggesting that phoenixin 14 has a protective role in liver function and lipid metabolism. Hematoxylin-eosin (HE) and Oil Red O staining of the liver showed that phoenixin 14 alleviated HFD-induced tissue damage and lipid deposition in the liver. Furthermore, the mice administered with phoenixin 14 had increased hepatic SOD activity, increased production of GSH and reduced MDA activity, as well as reduced production of TNF-α and IL-6 suggesting that phoenixin 14 exerts beneficial effects against inflammation and ROS. The findings suggest an explanation of how mechanistically phoenixin 14 ameliorated HFD-induced reduced activation of the SIRT1/AMPK and NRF2/HO-1 pathways.Conclusion: Collectively, this study revealed that phoenixin 14 exerts a protective effect in experimental NAFLD mice. Phoenixin could be of the interest in preventive modulation of NAFLD.Keywords: phoenixin 14, nonalcoholic fatty liver disease, NAFLD, oxidative stress, inflammation, NRF2/HO-1, SIRT1/AMPK